Polianthes tuberose Breeding in Indonesia - Sihombing, Donald (KnE Life Sciences, 2017)
Tuberose (Polianthus tuberosa) is an important ornamental plant in Indonesia that has been cultivated by farmers for a long time mainly in Java and North Sumatra provinces. However, the availability of new superior varieties is only a few so that the consumers only have a limited choice. Until now, there are three types of tuberose in Indonesia, which is distinguished by the type of flower namely single, semi-double and double flower. Some breeding efforts to obtain new varieties have been done through crossbreeding, mutation induction and selection to local cultivars. But the success on the crossbreeding of tuberose was only about 0.05%, as it can only be done in the direction of the single flower with double flowers. Because in the double flowers pistils are not found, the variability is very low. Nevertheless from these crossbreeding obtained 29 genotypes that showed differences in several characters, especially in the arrangements of flowers; and flower stalks straightness and rigidness. The other study indicates that each genotype has a different resistance levels against leaf spot disease (Xanthomonas sP.). Meanwhile, breeding of tuberose through mutation induction technique has not been widely studied. Application of gamma ray irradiation on tubers caused morphological damaged on Polyanthes, reduced bulb growth less than 30% and reduced the plant height more 400% than no treated plants (control). Polyploidy induced mutations by using colchicine led to changes in the length and diameter of the flowers and harvesting time. Until now, there is no result of the crossbreeding and mutation techniques that released as a new variety. Despite this, based on the positive selection breeding on local cultivars, there have been two superior genotypes released as new varieties namely Dian Arum (double flower type; origin of Cianjur, West Java) and Roro (semi double flower type; origin of Pasuruan, East Java). Keywords: Polianthes tuberosa ; breeding; local cultivars, new varieties,Dian Arum, Roro Anteng